Laparoskopske apendektomije v SB Slovenj Gradec - Breznikar, Brane (Endoskopska revija, 2005)
Background. The paper present the development of laparoscopic appendectomy at the Department of General and Abdominal Surgery of the Slovenj Gradec General Hospital over the past six years. During this period the repertoire of laparoscopic surgical procedures was extended to include laparoscopic appendectomy. Patients and methods. The study involved 64 patients undergoing laparoscopic-assisted and laparoscopic appendectomy. The procedure is simple and, in typical cases, cheaper than conventional surgery. Nondisposable trocars are used and a single suture is usually employed for two ligatures, which are mostly accomplished extracorporeally. In very thin children, a 5-mm disposable trocar is used. Results. Of the 64 patients admitted with appendicitis, seven presented with a perforated appendix. Laparoscopic revision and lavage were done in one female patient only. There were intraabdominal abscesses, and none of the patients died. Conclusion. Laparoscopic appendectomy has not yet become generally accepted as a standard procedure in patients with appendicitis. Some surgeons use laparoscopic approach in selected patients only, or, in cases of severe inflammation, convert to open procedure. The author completed all appendectomies laparoscopically.
Keywords: Apendektomija; Appendectomy; Laparoscopy; Laparoskopija; Treatment Outcome; Zdravljenje, izid; slepo črevo; laparoskopska kirurgija; kirurško zdravljenje